The Effect of Posaconazole and Isavuconazole on the Pharmacokinetics of Erdafitinib in Beagle Dogs by UPLC-MS/MS - Ruan, Lan-hong; Fan, Ling-ling; Wang, Kun; Zhang, Wan-qi; Wang, Xiao-jun; Qiu, Xiang-jun (Frontiers in Pharmacology, 2021)
Objective: A robust, quick, and reliable ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) method for the quantification of erdafitinib in beagle dog plasma was developed and validated to evaluate the changes of posaconazole and isavuconazole on the pharmacokinetics of erdafitinib in beagle dogs, respectively. Methods: This experiment adopted a three-period self-control experimental design. In the first period (group A), erdafitinib was orally administered to six beagle dogs at a dose of 4 mg/kg. In the second period (group B), the same six beagle dogs were orally given posaconazole at a dose of 7 mg/kg, and after 30 min, erdafitinib was orally given. In the third period (group C), isavuconazole at a dose of 7 mg/kg was given orally, and then, erdafitinib was orally given. At the different time points after erdafitinib was given in the three periods, the blood samples were collected. The concentration of erdafitinib was detected by the developed UPLC-MS/MS method. DAS 2.0 was used to calculate the pharmacokinetic parameters of erdafitinib. Results: Erdafitinib had a good linear relationship in the range of 1–500 ng/ml, and the lower limit of quantification was 1 ng/ml. The precision, accuracy, extraction recovery, matrix effect, and stability meet the requirements of the guiding principles. After erdafitinib was combined with posaconazole, the Cmax and AUC0→t of erdafitinib increased by 27.19% and 47.62%, respectively, and the t1/2 was prolonged to 6.33 h. After erdafitinib was combined with isavuconazole, the Cmax and AUC0→t of erdafitinib increased by 23.13% and 54.46%, respectively, and the t1/2 was prolonged to 6.31 h. Conclusion: A robust and reliable UPLC-MS/MS method was fully optimized and developed to detect the plasma concentration of erdafitinib in beagle dogs. Posaconazole and isaconazole could inhibit the metabolism of erdafitinib in beagle dogs and increase the plasma exposure of erdafitinib.